1982
DOI: 10.1111/j.1600-0609.1982.tb00575.x
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Cytosine Arabinoside in the Management of Refractory Acute Leukaemia

Abstract: 17 patients (age 15–58 years) with refractory acute leukaemia (14 AML, 3 ALL) were treated with high dose cytosine arabinoside (AraC) at a dose of 3000 mg/m2, twice daily for 6 d (13 patients with AraC alone, 4 patients with AraC and doxorubicin). 9 patients achieved complete remission (53 %) and 2 a partial remission. Although sophisticated isolation and blood banking facilities are required during the pancytopenic period, the toxicity of this treatment was acceptable. Vomiting, headache, somnolence, fever, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This approach is effective, and up to 70% of patients achieve remission, 1-6 but disease recurrence is common (80%) without consolidation with an allogeneic hematopoietic stem cell transplantation (HSCT) [7][8][9] The majority of relapses occur in the first year after diagnosis, 10-14 which is associated with lower chances of achieving and sustaining a second complete remission (CR), a prerequisite for a curative allogeneic transplant. [15][16][17][18][19] Therefore, well-tolerated and effective new drugs for the treatment of AML are desperately needed.Antimitotics are effective anticancer agents, with mechanisms of action that involve inhibition of tubulin polymerization (vinca alkaloids) or stabilization of microtubule polymers (taxanes). However, their lack of specificity results in dose-limiting neurotoxicity from disruption of microtubule dynamics in synaptic vesicles and Golgi apparatus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is effective, and up to 70% of patients achieve remission, 1-6 but disease recurrence is common (80%) without consolidation with an allogeneic hematopoietic stem cell transplantation (HSCT) [7][8][9] The majority of relapses occur in the first year after diagnosis, 10-14 which is associated with lower chances of achieving and sustaining a second complete remission (CR), a prerequisite for a curative allogeneic transplant. [15][16][17][18][19] Therefore, well-tolerated and effective new drugs for the treatment of AML are desperately needed.Antimitotics are effective anticancer agents, with mechanisms of action that involve inhibition of tubulin polymerization (vinca alkaloids) or stabilization of microtubule polymers (taxanes). However, their lack of specificity results in dose-limiting neurotoxicity from disruption of microtubule dynamics in synaptic vesicles and Golgi apparatus.…”
mentioning
confidence: 99%
“…Treatment of acute myeloid leukemia (AML) has been based for the past 30 years on a combination of an anthracycline and cytosine arabinoside. This approach is effective, and up to 70% of patients achieve remission,1‐6 but disease recurrence is common (80%) without consolidation with an allogeneic hematopoietic stem cell transplantation (HSCT)7‐9 The majority of relapses occur in the first year after diagnosis,10‐14 which is associated with lower chances of achieving and sustaining a second complete remission (CR), a prerequisite for a curative allogeneic transplant 15‐19. Therefore, well‐tolerated and effective new drugs for the treatment of AML are desperately needed.…”
mentioning
confidence: 99%
“…There are several human leukemia cell lines available, and only K562 cell line was selected to mimic the clinical situation, since this cell line was found to have higher baseline levels of M2 expression (data not shown), which is similar to those responders of AML patients treated with GTI-2040 and high-dose Ara-C (14). Ara-C is one of the most effective anticancer agents for the treatment of AML, and its therapeutic effect at low or high doses has been extensively studied (24)(25)(26)(27)(28)(29)(30)(31). It has been reported that the metabolism of Ara-C in vitro was greatly enhanced by RNR inhibitors, such as amidox and trimidox (32)(33)(34).…”
Section: Discussionmentioning
confidence: 54%
“…Our current results suggest that intensification of remission induction and consolidation might render the maintenance phase redundant. In adult ALL, CNS prophylaxisusing either cranial irradiation and intrathecal methotrexate or periodic intrathecal methotrexate alonehas been effective (16). Most of our patients received only 2 injections of intrathecal methotrexate, prophylactically.…”
Section: Discussionmentioning
confidence: 98%